Prevalence of headaches in individuals referred from primary care to secondary care - Rodrigues, Joismar Manuel; Caires, Vanessa Vilela; Fontoura, Kátia Beatriz Costa; Silva, Teresa Cristina Santos; Goulart, Simone Fonseca; Rocha, Cláudia Marcucci; Teixeira, Antônio Lúcio; Silva Junior, Ariovaldo Alberto da (Headache Medicine, 2011)
Background: Improve the quality of public health is a growing necessity today. Identifying reasons for medical referral (from general to specialized care) is a prelude for developing educational initiatives that have this goal. Objective: To estimate the prevalence of headaches as a cause of referral from the primary to the secondary level of public medical care. Methods: First-time referrals from four primary care units to neurology care were assessed. Results: Sample consisted of 587 individuals referred to neurology consultation. Headache was the cause of referral in 31.2% of the individuals; 79.2% of the headache cases were in women. Rates for other diseases were lower and are presented for benchmarking. Conclusion: Headache represented an important cause of demand for neurological care. Education initiatives on principles of headache management are necessary and may translate into decreased referral rates to neurologists.